Technological factors affecting the efficiency of accountants - Utharnsakul, Veerakij; Jarukaruna, Kingkan; Phaoduang, Somjai; Khumruang, Parichart; Saranapiboon, Panadda (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
The objective of this research was to examine the technological factors affecting the work efficiency of accountants. The population consisted of 76 accounting firms within the Nakhon Pathom Rajabhat University network. Questionnaires were employed as the research instrument for data collection. The statistics used in data analysis were only the descriptive statistics, and the multiple regression analysis. The results of the research showed technological factors have a positive effect on the efficiency of accountant (Y) in both aspects: software (X1) in terms of report preparation that should have flexibility according to the needs of the users (β = 0.510) and the hardware (X2) which uses a high-speed processing system, including a detailed display screen, good data input devices and stable computer operation can help increase the efficiency of the accountants (β = 0.287) were statistically significant at the 0.05 level, accounting for 53.40% of the variance. The resulting regression equation is as follows Y = 1.201 + 0.510(X1) + 0.287(X2) Article history: Received 27 June 2025 Accepted 5 November 2025 Accepted 7 November 2025 SIMILARITY INDEX = 5.82 %